PENGGUNAAN SOAL TES FORMATIF BERBASIS HOTS PADA PEMBELAJARAN TEKS PROSEDUR KELAS VII SMP - Yesi Maylani Kartiwi; Puji Astuti Shohheh (IKIP Siliwangi, 2023)
This research is motivated by the use of evaluation instruments which are carried out at the end of Indonesian language text learning mmaterials to avluaste the learning process and preparation of questions based on HOTS criteria. The aim of the study was to find out the application of HOTS based formatice test queations to learning procedural texts of class VII SMP. The research method used is qualitative, namely a research method tha focuses on quality or topics that are the most important thing in a product or service. The research instrument used is the test. The results of this stufy stated that out of 3 students, there were 23 students who got results in the forms of numbers below the KKM, so it could be said they did not have the skills high level thinking. The preparation of formative test questions based on the HOTS level applied to procedural text learning for class VII SMP can be used to evaluaste students proficiency in practicing higher order thinking skills, as well as helping studenta to be able to associate procedure texts with other types of texts in learning Indonesian.